PERMISSION RESTRICTION METHOD AND ALGORITHM IN DISTRIBUTED DATABASE - Sadikov Sh.M. (Journals Park Publishing, 2023)
The article analyzes the distributed database architecture, permission management methods, existing threats and vulnerabilities in the distributed database, features of permission restriction and their application in the distributed database, Role-based access control and Attribute-based access control methods. an enhanced, distributed resolution constraint algorithm is developed.
Keywords: distributed database, replication, access control, auditing and monitoring, rolebased access control (RBAC), ABAC model, encryption, users, resources, roles, permissions, distributed access restriction.